Sexual violence amongst rural women living with HIV: prevalence, forms and lived experiences at health facilities in southwestern Uganda - Mwebembezi, Gerald; Tusiime, Beneth Kaginda; Sikon, Ebenezer Felex; Sanyu, Nabatanzi Esther; Agaba, Kenneth; Nakaweesa, Scarlet Josephine; Rukundo, Godfrey Zari (Pan African Medical Journal One Health, 2022)
Introduction: sexual violence exists in different forms and contexts. It has different consequences including HIV/AIDS. There is limited information on the adoption of services to the victims. In this study, we investigated the prevalence, forms and personal experiences of sexual violence amongst women living with HIV/AIDS in rural southwestern Uganda. Methods: we conducted a cross-sectional survey among 324 women living with HIV. We also conducted 11 in-depth interviews among women living with HIV in the same area. We collected data on socio-demographics, participants’ experiences, forms of sexual violence, and the services for the victims. The in-depth interviews were conducted using a semi-structured interview guide. The quantitative data were analyzed at 95% confidence interval using Chi-square and logistic regression. Transcripts were cleaned were independently coded and any disagreements encountered during in the coding were resolved at each step. During the coding process, duplicates were removed. Similar quotes were grouped together under broad themes while ensuring inclusion of data from different sources. We used thematic content analysis to generate themes and sub-themes. Results: the mean age of the participants was 35.05 ± 12.21 years. Of the 324 women that participated in the study 68.8% were married 67.2% had primary level of education and were peasant farmers (70.1%). Sexual violence was experienced by 32.7% of the participants and this included sexual humiliation, forced genital touching and insertion of objects. Shame was the most commonly lived experience and sexual partners were the most common perpetrators of sexual violence. According to our findings, marriage (OR = 0.0250, 95%CI 0.069-0.905, p = 0.035) was a protective factor. Conclusion: sexual violence is commonly experienced by women living with HIV and attending health facilities in rural southwestern Uganda. Fear of shame negatively affects disclosure by the victims. Screening for sexual violence could be helpful in exposing the vice if it is integrated in routine HIV care for women.
Keywords: HIV/AIDS; Intimate partner violence; Sexual violence; Experiences; Southwestern Uganda